War crimes and spirituality: to prosecute or to forgive and reconcile (Law and Safety, 2023)
Conducting investigations on war crimes has a clear goal of establishing facts on crimes, perpetrators, and victims. On the other hand, the question of forgiveness and reconciliation, as essential conditions for re-establishing the coexistence of former parties at war which continue to live together, in the same community, country, and society (or next to each other), is something completely different. Investigating crimes, establishing facts, and finding and prosecuting individuals for committing those crimes, is an exact, measurable category. Forgiveness and reconciliation are not. By questioning the real effects of war crimes trials in post-conflict societies, this article argues that, for a peaceful and lasting foundation for the future life in post-conflict societies, a legal approach to the atrocities committed is not sufficient. In addition, there is a need to find a way to forgiveness and reconciliation, without which societies can always return to the “dark past”. The New Testament says that only the truth will set us free, but is that immanent to the human being? Can a human being truly forgive, or is mercy only reserved for divine beings? Can and should the victims forgive their torturers, the ones who burned down their homes, killed their beloved ones, destroyed their lives and burdened them with memories that do not fade away? In countries where past conflict resulted in mass atrocities and where, following some peace agreement, the former parties at war did not go separate ways but continued to live in the same country, this inevitable reality is a burden, if not even a risk to the existence and rebuilding of the post-conflict society. To a great extent, the situation is the same for neighboring societies (countries). But no matter what, the question is whether war crimes trials and punishments for war criminals will eliminate the consequences of those crimes, allow the victims to free themselves from that victimhood, and societies at war to find peace and rebuild.
Keywords: war crimes; justice; spirituality; forgiveness; reconciliation.